(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
The article deals with the psychological preparation of sports gymnasts in international tournaments of various levels. A very large share of success depends on this preparation. Emotional stress can reduce the effectiveness of sports exercises, which will lead to a deterioration in performance, and consequently, to a depressive mood.